Growth of gallium nitride thin film with the aid of polymethyl methacrylate - C.Y., Fong; S.S., Ng; F.K., Yam; Abu Hassan, H.; Hassan, Z. (Universiti Kebangsaan Malaysia, 2014)
Wurtzite structure gallium nitride (GaN) thin film was grown on a c-plane sapphire (0001) substrate through spin coating method followed by nitridation process. Readily available and cheap gallium (III) nitrate hydrate (Ga(NO3)3·xH2O) powder was used as the gallium source. Besides that, ethanol-based precursor solution which has better wetting properties and fast evaporation rate was prepared. In addition, a thin layer of polymethyl methacrylate was introduced as a bonding adhesive layer for the growth of the GaN thin film. X-ray diffraction results indicated that the deposited film consists of nanocrystallite GaN with hexagonal wurtzite structure. Field-emission scanning electron microscopy showed the morphologies of the small and well-defined spherical grains that coated on the substrate. The synthesized GaN thin film demonstrated a pronounced and broad exciton peak at 380 nm in Photoluminescence spectrum. Raman scattering measurements showed two features that correspond to the E2 (high) and A1 (LO) phonon modes of the hexagonal GaN.